Effects of repeated low-level red light therapy on myopia progression in children: a systematic review and meta-analysis - Fan, Haobo; Yu, Jia; Jiang, Aiming; Wei, Qiumei; Zhang, Xuemin; Xie, Airui; Duan, Junguo (Frontiers in Medicine, 2025)
PurposeThis study aimed to evaluate the effects of repeated low-level red light (RLRL) therapy in intervening in the progression of myopia in children.MethodsWe searched PubMed, the Cochrane Library, Embase, Web of Science, and CNKI databases for relevant studies published from the inception of the databases to 30 April 2025. Subsequently, studies were screened according to the inclusion and exclusion criteria, and basic information and outcome data of the included studies were recorded. The risk of bias in randomized controlled trials (RCTs) and cohort studies was assessed using the RoB 2.0 tool and the NOS, respectively. Finally, meta-analysis was performed using RevMan 5.4, and meta-regression, sensitivity analysis, and publication bias assessment were conducted using STATA 17.ResultsA total of 20 studies were included in this study, involving 2,638 Chinese children, aged from 3 to 16 years, with a baseline spherical equivalent refraction (SER) ranging between +0.75 and −10.00 diopters. A meta-analysis showed that, compared with the control group, the RLRL group had a slower axial elongation, a lower progression of SER, and a greater increase in subfoveal choroidal thickness (SFCT). The changes in axial length (AL) at the 6th, 12th, and 24th months of follow-up in the RLRL group relative to the control group were −0.22 mm (95% CI: −0.25, −0.18; p < 0.00001), −0.30 mm (95% CI: −0.36, −0.24; p < 0.00001), and −0.61 mm (95% CI: −0.71, −0.52; p < 0.00001), respectively. The corresponding changes in SER at these time points were 0.40 D (95% CI: 0.31, 0.50; p < 0.00001), 0.61 D (95% CI: 0.47, 0.76; p < 0.00001), and 1.33 D (95% CI: 0.62, 2.03; p = 0.0002). Additionally, the changes in SFCT at the 6th and 12th months of follow-up were 31.21 μm (95% CI: 22.03, 40.38; p < 0.00001) and 29.72 μm (95% CI: 19.53, 39.92; p < 0.00001), respectively. Meta-regression and subgroup analysis revealed that the baseline SER and treatment frequency primarily contributed to the heterogeneity observed in this study.ConclusionThis meta-analysis confirmed that RLRL therapy can effectively delay the progression of myopia in children during a 6–24 months follow-up, and the efficacy appears to be directly related to the degree of the baseline myopia and the LRLR treatment frequency. However, a causal relationship has been suggested between retinal damage and LRLR treatments, which requires further investigations.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD420251018947.